Mitochondrial sirtuins, metabolism, and aging. (April 2022) - Ji, Zhejun; Liu, Guang-Hui; Qu, Jing
Abstract: Maintaining metabolic homeostasis is essential for cellular and organismal health throughout life. Multiple signaling pathways that regulate metabolism also play critical roles in aging, such as PI3K/AKT, mTOR, AMPK, and sirtuins (SIRTs). Among them, sirtuins are known as a protein family with versatile functions, such as metabolic control, epigenetic modification and lifespan extension. Therefore, by understanding how sirtuins regulate metabolic processes, we can start to understand how they slow down or accelerate biological aging from the perspectives of metabolic regulation. Here, we review the biology of SIRT3, SIRT4, and SIRT5, known as the mitochondrial sirtuins due to their localization in the mitochondrial matrix. First, we will discuss canonical pathways that regulate metabolism more broadly and how these are integrated with aging regulation. Then, we will summarize the current knowledge about functional differences between SIRT3, SIRT4, and SIRT5 in metabolic control and integration in signaling networks. Finally, we will discuss how mitochondrial sirtuins regulate processes associated with aging and aging-related diseases.